Sentinel Surveillance Reveals Emerging Daptomycin-Resistant ST736 Enterococcus faecium and Multiple Mechanisms of Linezolid Resistance in Enterococci in the United States - Gargis, Amy S.; Spicer, Lori M.; Kent, Alyssa G.; Zhu, Wenming; Campbell, Davina; McAllister, Gillian; Ewing, Thomas O.; Albrecht, Valerie; Stevens, Valerie A.; Sheth, Mili; Padilla, Jasmine; Batra, Dhwani; et al. (Frontiers in Microbiology, 2022)
Enterococcus faecalis and faecium with resistance to daptomycin and/or linezolid are emerging globally. We present the genomic characterization of daptomycin- and linezolid-resistant E. faecalis and E. faecium surveillance isolates from the United States, 2013-2016. Daptomycin resistance was low among E. faecalis (2/364, 0.5%) and E. faecium (17/344, 5%). The majority (71%, 12/17) of daptomycin-resistant E. faecium isolates belonged to the emerging ST736 clone and contained mutations in liaFSR and cls previously associated with resistance. However, 1/2 E. faecalis and 3/17 E. faecium did not contain these mutations previously associated with daptomycin resistance. Linezolid resistance was rare among E. faecalis (1/364, 0.3%) and E. faecium (2/344, 0.6%). These two E. faecium isolates, one of which was also resistant to daptomycin and vancomycin, contained the 23S rRNA mutation (G2576T) associated with linezolid resistance. Long-read sequencing revealed the linezolid-resistant E. faecalis isolate contained chromosomal- and plasmid-encoded copies of optrA. The chromosomal optrA was located on the recently described Tn6674 multiresistance transposon. The second copy of optrA was encoded on an ~65 kb mosaic plasmid, with component regions sharing high sequence identity to optrA-encoding multiresistance plasmids of animal origin. The optrA-encoding plasmid contained open reading frames predicted to encode proteins associated with a pheromone-responsive plasmid transfer system, and filter mating experiments confirmed the plasmid was conjugative. Continued surveillance of enterococci is necessary to assess the prevalence and trends in daptomycin and linezolid resistance in the United States, characterize resistance mechanisms and how they transfer, and monitor for emerging sequence types associated with resistance.